“I pictured my little sister when writing” – Teacher and Student Experiences with Training Audience Awareness in a Television Studies Seminar - Schmidt, Regina Leonie (Journal of Academic Writing, 2020)
Training audience awareness is a significant but challenging task for teaching academic writing. To integrate the teaching of television studies with writing skills, I designed a BA seminar when working as a lecturer in the English department of a German university in 2015. I present my experience with and my students’ evaluation of training audience awareness as part of this seminar. The evaluations confirmed students’ increased awareness of the importance of incorporating audience-directed elements in writing, but indicated that the task had created obstacles, for example, regarding students’ reading comprehension. I retrospectively analyze my teaching approach and discuss possible reasons for my students’ success and difficulties with the writing assignment, and make suggestions for changes that may have better supported their learning process. I, therewith, aim to foster the integration of teaching writing within, across, and beyond disciplinary audiences in discipline-specific courses.